Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,\frac{1212}{1515}+\frac{1212}{3535}+\frac{1212}{6363}+\frac{1212}{9999}=\frac{12}{15}+\frac{12}{35}+\frac{12}{63}+\frac{12}{99}=6\left(\frac{2}{15}+\frac{2}{35}+\frac{2}{63}+\frac{2}{99}\right)=6\left(\frac{2}{3.5}+\frac{2}{5.7}+\frac{2}{7.9}+\frac{2}{9.11}\right).Tacocongthuc:\frac{1}{n}-\frac{1}{n+k}=\frac{k}{n\left(n+k\right)}\Rightarrow\frac{1212}{1515}+\frac{1212}{3535}+\frac{1212}{6363}+\frac{1212}{9999}=6\left(\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-.....-\frac{1}{11}\right)=6\left(\frac{1}{3}-\frac{1}{11}\right)=\frac{48}{33}=\frac{16}{11}\)
\(2,\left(x+1\right)+\left(x+2\right)+.....+\left(x+211\right)=211x+\left(1+2+....+211\right)=211x+\frac{212.211}{2}=211x+22366=23632\Leftrightarrow211x=23632-22366=1266\Leftrightarrow x=6\)
a, \(14:\left(4\frac{2}{3}:1\frac{5}{9}\right)+14:\left(\frac{2}{3}+\frac{8}{9}\right)\)
=> \(14:\frac{28}{9}+14:\frac{14}{9}=>14.\frac{9}{28}+14.\frac{9}{14}\)
=> 14. ( \(\frac{9}{28}+\frac{9}{14}\) )
=> \(14.\frac{27}{28}=\frac{419}{28}\)
b, \(\frac{1212}{1515}+\frac{1212}{3535}+\frac{1212}{6363}+\frac{1212}{9999}\)
=> \(\frac{4}{5}+\frac{12}{35}+\frac{4}{21}+\frac{4}{33}\)
=> \(\frac{8}{7}+\frac{24}{77}=\frac{16}{11}\)
bài 2 :
( x + 1 ) + ( x + 2 ) + ... + ( x + 211 ) = 23632
=> ( x + x + x + ... + x ) + ( 1 + 2 + 3 + ... + 211 ) = 23632
=> 211x + 22366 = 23632
=> 211x = 23632 - 22366
=> 211x = 1266
=> x = 1266 : 211
x = 6
(-6,17 +3+5/9-2-36/97)*(1/3-1/4-1/12)=(-6,17+3+5/9-2-36/97)*(4/12-3/12-1/12)=(-6,17+3+5/9-2-36/97)*0=0
Bài 1
a) \(\frac{1}{2}+\frac{3}{8}:3-\frac{3}{16}.2^3 \)
\(=\frac{1}{2}+\frac{3}{8}.\frac{1}{3}-\frac{3}{16}.8 \)
\(=\frac{1}{2}+\frac{1}{8}-\frac{3}{2} \)
\(=\frac{4}{8}+\frac{1}{8}-\frac{12}{8} \)
\(=\frac{-7}{8}\)
a) ( x + 3 )3 : 3 - 1 = -10
( x + 3 )3 : 3 = -10 + 1
( x + 3 )3 = -9 * 3
x + 3 = \(\sqrt[3]{-27}\)
x = -3 - 3
x = -6
b) 3 | x - 1 | + 5 = 17
3 | x - 1 | = 17 - 5
| x - 1 | = 12 : 3
| x - 1 | = 4
( 1 ) x - 1 > 0 => x - 1 = 4 => x = 5
( 2 ) x - 1 < 0 => x - 1 = -4 => x = -3
Vậy S = { -3 ; 5 }
\(a,\frac{1}{3}:\left(2x-1\right)=-\frac{4}{21}\)
\(< =>\frac{1}{3}.\frac{1}{2x-1}=-\frac{4}{21}\)
\(< =>\frac{1}{6x-3}=-\frac{4}{21}\)
\(< =>\frac{1}{6x-3}+\frac{4}{21}=0\)
\(< =>21-24x+12=0\)
\(< =>33-24x=0\)
\(< =>x=\frac{33}{24}\)
\(b,\frac{17}{2}-|x-\frac{3}{4}|=\frac{-7}{4}\)
\(< =>|x-\frac{3}{4}|=\frac{17}{2}+\frac{7}{4}=\frac{41}{4}\)
\(< =>\orbr{\begin{cases}x-\frac{3}{4}=\frac{41}{4}\\x-\frac{3}{4}=-\frac{41}{4}\end{cases}}\)
\(< =>\orbr{\begin{cases}x=\frac{41}{4}+\frac{3}{4}\\x=-\frac{41}{4}+\frac{3}{4}\end{cases}}\)
\(< =>\orbr{\begin{cases}x=11\\x=-\frac{19}{2}\end{cases}}\)
a, \(\frac{1}{3}:\left(2x-1\right)=-\frac{4}{21}\)
\(\Leftrightarrow\frac{1}{3}.\frac{1}{2x-1}=-\frac{4}{21}\)
\(\Leftrightarrow\frac{1}{6x-3}=-\frac{4}{21}\)
\(\Leftrightarrow21=-24x+12\)
\(\Leftrightarrow-24x=9\Leftrightarrow x=-\frac{3}{8}\)
b, \(\frac{17}{2}-\left|x-\frac{3}{4}\right|=-\frac{7}{4}\)
\(\Leftrightarrow\left|x-\frac{3}{4}\right|=\frac{41}{4}\)
\(\Leftrightarrow\orbr{\begin{cases}x-\frac{3}{4}=\frac{41}{4}\\x-\frac{3}{4}=-\frac{41}{4}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=11\\x=-\frac{19}{2}\end{cases}}}\)
\(\frac{1}{2}\times(x-\frac{1}{3})+\left(\frac{1}{3}-x\right)=0\)
\(\frac{1}{2}\cdot\left(x-\frac{1}{3}\right)-x\left(x-\frac{1}{3}\right)=0\)
\(\left(x-\frac{1}{3}\right)\left(\frac{1}{2}-x\right)=0\)
\(\left(x-\frac{1}{3}\right)=0\)và \(\left(\frac{1}{2}-x\right)=0\)
TH1